Cardiac Function After Tetralogy of Fallot/Complete Atrioventricular Canal Repair. (March 2017) - Stephens, Elizabeth H.; Tingo, Jennifer; Najjar, Marc; Yilmaz, Betul; Levasseur, Stéphanie; Dayton, Jeffrey D.; Mosca, Ralph S.; Chai, Paul; Quaegebeur, Jan M.; Bacha, Emile A.
Background: Repair of complete atrioventricular canal (CAVC) with tetralogy of Fallot (TOF) is a challenging operation increasingly being performed as a complete, primary repair in infancy. Previous studies have focused on perioperative outcomes; however, midterm valve function, ventricular function, and residual obstruction have received little attention. Methods: We retrospectively reviewed 20 patients who underwent CAVC/TOF repair (January 2005 to December 2014). A two-patch repair was used in all patients to correct the CAVC defect. Tetralogy of Fallot repair included transannular patch in 11 (65%) patients and valve-sparing in 6 (35%) patients. Results: The average age at surgery was 72 ± 122 weeks, 40% were male, and 80% had trisomy 21. Mean echo follow-up was 3.0 ± 3.0 years. There were no in-hospital or late mortalities. The rate of reoperation was 20%. At the latest follow-up, moderate left atrioventricular valve regurgitation was present in three (15%) patients and mild stenosis present in seven (35%) patients. One (5%) patient had moderate right ventricular outflow tract (RVOT) obstruction. The valve-sparing population was smaller at the time of surgery than the non-valve-sparing cohort (body surface area: 0.28 ± 0.04 vs 0.42 ± 0.11, P = .002) and less likely to have had a previous shunt (0% vs 64%, P = .01). Among the valve-sparing patients (six), at the latest follow-up, moderate pulmonary insufficiency was present in two (33%) patients. Conclusion: Repair of CAVC concomitant with TOF can be performed with low mortality and acceptable perioperative morbidity. Management of the RVOT remains a challenge for the long term.